Peri-pandemic physical activity in Southeast Asia a narrative review - Empleo-Pacres, Joan Grace (2022)
To stifle widespread transmission of the COVID-19 virus, Southeast Asian governments initiated lockdowns and quarantines that severely limited human mobility and people’s engagement in healthful and sufficient physical activity (PA). What was the state of PA in Southeast Asia during the pandemic? This narrative review answered this major question by reviewing relevant studies identified through a keyword search in online research databases, the results of which were then filtered according inclusion criteria and topic relevance before the final set of articles were summarized and synthesized. The findings of 13 studies, covering only five Southeast Asian nations, make up the bulk of this narrative review. Some of the studies reported associations between PA and mental health (especially anxiety and depression), health literacy, Health-Related Quality of Life, and sleep. Other studies discussed the use of technology for PA, problems related to physical activity, and the importance of PA to the elderly during the pandemic. More studies need to be done about peri-pandemic PA, particularly about the factors, systems, and technologies affecting PA levels and sedentary behavior from pre- to peri-pandemic periods so that stakeholders can improve maintenance-level PA, preserve increased PA levels, increase PA levels where such have decreased, and keep sedentary behavior low all throughout. Peri-pandemic sedentary behavior also needs more attention, since physical inactivity and sedentary behavior, although distinct from each other, usually accompany each other, are correlated, and have significant impact on human health.
Keywords: Physical activity; COVID-19 pandemic; Sedentary behavior